Measurement and Numerical Simulation of Temperature Distributions of a Micro-Tubular SOEC during H2O/CO2 Co-Electrolysis. (30th May 2017) - Maeda, Atsushi; Watanabe, Kentaro; Araki, Takuto; Mori, Masashi
Abstract : Co-electrolysis by SOEC can generate CO and H2 from both CO2 and H2 O at the same time. For practical use of SOEC, it is important to know temperature distributions, which affect the durability of the cell. In this study, temperature distributions of air electrode surface were measured by a thermal imaging camera to understand the temperature distribution in SOEC during co-electrolysis. Additionally, the temperatures were measured directly at three points by K-type thermocouples for comparing the temperatures measured by the camera. Furthermore, a two dimensional numerical model of a SOEC was developed and compared to the measured temperature distributions.